IMPLEMENTASI PKPU NOMOR 65 TAHUN 2009 OLEH KPU KABUPATEN MOJOKERTO PADA PEMILU 2024 DI KABUPATEN MOJOKERTO - Hasan Afandi, Ahmad; Yudha Utama, Jenny; Viona Maharani, Julieta (Universitas Islam Majapahit, Indonesia, 2024)
This study aims to determine and analyze the implementation of PKPU Number 65 of 2009 by the Mojokerto Regency KPU in the 2024 election in Mojokerto Regency, to determine the inhibiting and supporting factors of the Mojokerto Regency KPU in implementing PKPU Number 65 of 2009 in the election with face-to-face activities including socialization, parades, smart election houses. This study uses Anthony Giddens' Structuration theory as an analytical tool in a structural perspective. The method used is a case study, with data collection techniques through observation, documentation, and interviews. As well as selected informants, namely the Chairperson of the Mojokerto Regency KPU, Chair of the Sosdiklih Division, and Representatives of Generation Z